Attitudes of Female University Students towards Studying English Language Courses via Virtual Classes - Makki, Alwia Awad (Journal of Ecohumanism, 2025)
Teaching English Language through virtual classrooms is regarded as a new experience. Consequently, a scientific and methodical investigation is needed to understand its advantages, disadvantages, problems and level of satisfaction among students. This study seeks to discover the attitudes of female EFL students at Taif University concerning the utilization of virtual classrooms for English courses instructions. A descriptive survey research approach of a quantitative nature was employed. The study took place at Taif University in Saudi Arabia. Along with two chosen colleges for the study: Applied College and Turabah University College. All students participated in the same course via online classes. In total, the sample size for this study was 227 female students. The samples were chosen from the entire group of the participants which consisted of 868 individuals. The instrument utilized for gathering data was a 26-items questionnaire. According to the analysis of the students’ responses, the study reflected that students have positive attitudes towards learning English via virtual classrooms. Moreover; the quantitative data showed that students expressed higher satisfaction with online classrooms and preferred this approach for learning the English Language. Nevertheless; technical issues hindered some of the students from utilizing virtual classrooms efficiently. The limitations of the study highlight the need for future research to explore EFL virtual classrooms among diverse students groups and context, utilizing both quantitative and qualitative approaches. Also teachers should consider students’ views and feelings when delivering EFL materials.